A Comparison of Intravitreal Bevacizumab and Steroid Activity in an Experimental Uveitis Model. (2nd December 2015) - Ayyıldız, Onder; Durukan, Ali Hakan; Ozgurtas, Taner; Gunal, Armagan
Abstract: Purpose : To compare intravitreal bevacizumab (IVB) and steroid activity in an experimental uveitis (EU) model. Materials and methods : EU was induced by intravitreal injection of bovine serum albumin (BSA) at baseline. Rabbits were randomly divided into three groups ( n  = 8) according to treatment with a single dose of IVB, steroid or saline on day 3. Aqueous humor (AH) samples were collected periodically (baseline and days 1, 3, 10 and 33). Rabbits were sacrified and eyes were enucleated for histopathology on day 33. AH vascular endothelial growth factor (VEGF) levels and histopathological changes were subjected to statistical analysis. Results : VEGF levels increased significantly after BSA injection (day 1) when compared with baseline in all three groups. Mean VEGF levels were 794.46 pg/mL, 777.91 pg/mL and 872 pg/mL for IVB, steroid and control groups, respectively ( p  = 0.002, p  = 0.019 and p  = 0.014). Seven days after treatment (day 10), VEGF levels decreased significantly in both treatment groups. Mean VEGF levels were 0 pg/mL, 292 pg/mL and 872 pg/mL, repectively ( p  < 0.001, p  = 0.016 and p  = 0.12). On day 33, the VEGF levels and inflammation had returned to baseline levels in both treatment groups, whereas no decrease in inflammation was observed in the control group. The histopathological evaluation revealed a mild congestion in ciliary tissue with a normal retina and choroidea in IVB group, a mild congestion in ciliary tissue with moderate inflammation in the posterior vitreus and a normal retina in steroid group and a severe inflammation in ciliary tissue with moderate inflammation in the retina in control group. Conclusions : These findings suggest that IVB may be used as an alternative to steroid treatment to reduce the acute effects of inflammation in patients with uveitis in whom intraocular steroids are contraindicated.